NanoFN10: A High-Contrast Turn-On Fluorescence Nanoprobe for Multiphoton Singlet Oxygen Imaging. - Zanocco, Renzo P.; Nájera-Albendín, Francisco; Pérez-Inestrosa, Ezequiel; Zanocco, Antonio L.; Lemp, Else; Nonell-Marrugat, Santiago (MDPI, 2023)
An “off-on” fluorescent nanoprobe for near-infrared multiphoton imaging of singlet oxygen has been developed. The nanoprobe comprises a naphthoxazole fluorescent unit and a singlet-oxygen-sensitive furan derivative attached to the surface of mesoporous silica nanoparticles. In solution, the fluorescence of the nanoprobe increases upon reaction with singlet oxygen both under one- and multiphoton excitation, with fluorescence enhancements up to 180-fold. The nanoprobe can be readily internalized by macrophage cells and is capable of imaging intracellular singlet oxygen under multiphoton excitation.
Keywords: Procesos multifotónicos; Sondas fluorescentes; Singlet oxygen; Fluorescent nanoprobe; Multiphoton excitation